2019
DOI: 10.1108/ijrdm-07-2018-0119
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of using cross-docking in the retail supply chain

Abstract: Purpose The purpose of this paper is to investigate the costs/benefits of implementing the cross-docking strategy in a retail supply chain context using a cost model. In particular, the effects of using different typologies of cross-docking compared to traditional warehousing are investigated, taking into consideration an actual case study of a fast-moving consumer goods (FMCG) company and a major French retailer. Design/methodology/approach The research is based on a case study of an FMCG company and a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…In addition, manufacturers also benefit, since the JIT technology can be implemented in both directions of flows. Accordingly, new cross-docking and pick-by-line technologies are being introduced at DC [23]. The criteria for economic efficiency [24] when maximizing the 3PL operator's profit can be the minimization of costs for the DC scale and the balance between possible costs (for example, for the factors of demurrage and detention or for contractual penalties for non-delivery or late shipment) [25].…”
Section: Theoretical Foundations and Methodology 21 Literature Reviewmentioning
confidence: 99%
“…In addition, manufacturers also benefit, since the JIT technology can be implemented in both directions of flows. Accordingly, new cross-docking and pick-by-line technologies are being introduced at DC [23]. The criteria for economic efficiency [24] when maximizing the 3PL operator's profit can be the minimization of costs for the DC scale and the balance between possible costs (for example, for the factors of demurrage and detention or for contractual penalties for non-delivery or late shipment) [25].…”
Section: Theoretical Foundations and Methodology 21 Literature Reviewmentioning
confidence: 99%
“…Some store chains like grocery chains, bring the products into one location and re-split them to multiple locations at different stores. A study of cross-docking in the retail sector [70] examined the costs/benefits of implementing the cross-docking strategy in a major French retail supply chain, in particular, fast-moving consumer goods.…”
Section: Implications Of Research In Each Clustermentioning
confidence: 99%
“…Based on a survey conducted among young people, the authors pointed out that the attempt to introduce self-service technology in retail is not accepted by Croatian consumers and that they consider it as an auxiliary register, mainly due to frequent technical failures, requiring further measures to improve computer systems. The optimization of storage systems in retail networks in France, based on the application of the cross-docking strategy, was analysed by Benrqya (2019). The author demonstrated that significant reductions in storage costs can be achieved at the supermarket level, by combining cross-docking methods with traditional storage systems.…”
Section: Literature Reviewmentioning
confidence: 99%